Legal Protection For Consumers Against The Potential Harm Caused By Promotions Using Deepfakes - Hasibuan, Ali Huristak Hartawan; David Novan Setyawan; Yanuriansyah Ar Rasyid (Jurnal Ilmu Hukum Kyadiren, 2025)
This research investigates the use of deepfakes in promotions and legal protection for consumers against potential harm caused by promotions using deepfakes. The use of deepfakes in promotions is a form of information manipulation that can potentially mislead consumers significantly. This research aims to determine the regulation of the use of deepfakes in promotions and whether the law can protect consumers against promotions that use deepfakes. This research uses a normative legal approach, analyzing legal principles and statutory regulations, especially those in the Consumer Protection Law and the Information and Electronic Transactions Law. The results of this research are that the Consumer Protection Law and the Information and Electronic Transactions Law can become a regulatory framework for using deepfakes in promotions. Legal protection for consumers can be carried out through two approaches, namely preventive legal protection and repressive legal protection